Pendapatan Usahatani Ubi Jalar (Ipomoea batatas L.) di Kecamatan Nglegok Kabupaten Blitar - Nastiti Winahyu; Melinda Nur Dianasari (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2023)
Sweet potato (Ipomoea batatas L.) is one of the commodities as a substitute for staple foods. Provision of sweet potatoes can be used for a variety of local food ingredients that can be consumed in the form of sweet potatoes and processed products. This availability can be encouraged by increasing production and farming efficiency. The purpose of this study is to analyze the sweet potato business income in Nglegok District, Blitar Regency. ResultsThe analysis shows that farming is run profitably. The R/C ratio obtained a value of 1.86 which means that every one rupiah of costs incurred generates revenue of Rp. 1.86 so that sweet potato farming is feasible to cultivate.